(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to investigate cardiovascular responses to training BODY PUMP, along with the levels of heart rates among adult non-athletes. The sample comprised 15 students (n = 15) with a mean age of 30.5 ± 8.7. Data were collected from pre-school, during class, and salutes to the end of each song the workout of BODY PUMP, during the 74 mix. After obtaining these data, we performed a descriptive statistical treatment, aiming to define the profile of the group. Applied the statistical test of arithmetic mean, standard deviation, distortion and percentage of heart rates, because through them you can compare the group data, looking for differences in central tendency, variability, or whatever. The results indicate that there is homogeneity statistically significant between the heart rate levels of students. However, we can conclude that the BODY PUMP is an excellent way of improving cardio respiratory fitness training, he obtained statistically significant results in comparison with the students of the training, thus helping to break the myth that only the activity serves as an exercise for training reduction of body fat. The results also speak for those who for various reasons cannot or do not like training in weight rooms, thus providing a new option of training in gyms, clubs, spa or similar places.